Solidified Floating Organic Drop Microextraction for the Detection of Trace Amount of Lead in Various Samples by Electrothermal Atomic Absorption Spectrometry - Oya Aydın Urucu; Şeyda Dönmez; Ece Kök Yetimoğlu (Journal of Analytical Methods in Chemistry)
A novel method was developed for determination of trace amounts of lead in water and food samples. Solidified floating organic drop microextraction was used to preconcentrate the lead ion. After the analyte was complexed with 1-(2-pyridylazo)-2-naphthol, undecanol and acetonitrile were added as extraction and dispersive solvent, respectively. Variables such as pH, volumes of extraction and dispersive solvents, and concentration of chelating agent were optimized. Under the optimum conditions, the detection limit of Pb (II) was determined as 0.042 µg L−1 with an enrichment factor of 300. The relative standard deviation is <10%. Accuracy of the developed procedure was evaluated by the analysis of certified reference material of human hair (NCS DC 73347) and wastewater (SPS-WW2) with satisfactory results. The developed procedure was then successfully applied to biscuit and water samples for detection of Pb (II) ions.